Fault type classification using pattern recognition - Abdul Bar, Shafini (2014)
An electromagnetic transient in power systems is due to various disturbances in the transmission line, such as a fault on the transmission line, it is very important. Fault occurs when two or more conductors in contact with each other or the ground in a three-phase system , the fault is classified as single line to ground fault , line to line fault , double line to ground fault and three phase fault. Fault identification of power system using the information presented by the wavelet analysis of transient power system is proposed to detect the type of line or wave transmission fault. The work presented in this study focuses on identifying simple power system fault. Discrete wavelet transform (DWT) analysis of transient disturbances caused due to the fault done by the creation of the standards, the maximum detail coefficients and energy signals for each type of fault simulation is simple in its nature and is used to distinguish the type of fault